A Theoretical and Experimental Study on Esterification of Citric Acid with the Primary Alcohols and the Hydroxyl Groups of Cellulose Chain (n = 1-2) in Parched Condition - Dang T. Nguyen; Quan T. Pham (Journal of Chemistry)
Esterification of citric acid (CA) with the primary alcohols and the hydroxyl groups of cellulose chain (n = 1-2) in parched condition were investigated by using density functional theory (DFT) method and a two-layer ONIOM approach. Geometry and energy of reactants, products, and transition state (TS) structures were optimized at B3LYP/6-311g (d, p) level and ONIOM (B3LYP/6-311g (d, p):PM3MM) level. The computational results show that the esterification occurs in the two main steps: the first step is the dehydration reaction of CA to form anhydrides of 5-membered ring and 6-membered ring and the second step is the ring opening reaction with the hydroxyl –OH groups to form the ester products. The energy barrier of dehydration reaction step is much higher than that of ring opening reaction step. Effect of substituent R in primary alcohol R-CH2OH (R: CH=CH2, CH2NHCH3, CH2OCH3, CH2Cl) and cellulose chain (1G, 2G) on the reactivity, which has negative inductive effect –I, is significant. The combination of calculation data and experiment data were applied to make findings more rigorous. The activation energy of CA was determined by using differential scanning calorimetry (DSC) and thermal gravimetric (TG) analysis to be Eaexp = 47.8 kcal/mol; the experimental data favoured the dehydration reaction step of CA.